(untitled) (Laisvalaikio tyrimai, 2018)
Research background. According to the United Nations Convention on The Rights of Persons with Disabilities (ratified in Lithuania in 2010), inclusion as well as participation in sports activities enable people with disabilities to disclose their needs as well as create a possibility to raise problems and suggest appropriate solutions. In addition, people with disabilities become more visible and that causes social dialogue between disabled people and “healthy” society. However, disabled people face conditions that either restrict/limit or encourage participating in particular areas. L. Samsonienė et al. (2010) state that participation of disabled people in sports depends on three interrelated groups of factors: health condition, environment (physical and social) as well as individual aspects such as gender, age, motivation, upbringing etc. According to V. Kavaliauskas and J. V. Vaitkevičius (2013), participation in sports activities of disabled people is caused by willingness to enhance their health and by the need of self-actualization. Researchers (Samsonienė et al., 2010; Skučas, 2010; Skučas, Vozbutas, 2008; RuolytėVerschoore, 2012; Požėrienė et al., 2013) show that people with disabilities who take part into some kind of activities are more likely to succeed taking an advantage of opportunities than disabled people who are under-motivated to participate and emphasize environmental restriction as well. The aim of study was to disclose experience as well as attitudes towards participation in sports of disabled participants. Methods. Semi structured interview was used in this study. The sample included twelve people (informants) with physical or sensory disabilities. The essential sampling criterion was experience (current or former) in some kind of sports activities regardless of its professional level. The research was carried out in April-May, 2014. Semi structured interview was based on these guidelines: 1) motives and significance of participation in sports, 2) advantages of participation in sports and factors limiting participation, 3) evaluation of sport organizations as well as qualification of coaches. Analysis of interviews was based both on qualitative content analysis and comparative analysis. Results. Participation of people with disabilities in sports activities is encouraged by friends, relatives, family members; however one of the most important factors is motivation of disabled people. Participation in physical activity leads not only to positive changes in personal health but also to selfrealization and integration/socialization of individuals. However, people with disabilities face internal as well as external obstacles by taking part in sports. One of the most important internal issues is a lack of motivation, health problems, traumas etc. Unsuitable environment for disabled people and low funding/support of sports organizations for people with disabilities limit their opportunities to participate in sports. It is noted that coaches lack communication and working experience with disabled people. Keywords: people with disabilities, participation, sports activities.